2021
DOI: 10.1093/bjs/znab361.187
|View full text |Cite
|
Sign up to set email alerts
|

SP10.2.6 The Quantitative Impact of COVID-19 on surgical training in the United Kingdom

Abstract: Aims COVID-19 has had a global impact on all aspects of healthcare including surgical teaching and training. This study aimed to quantify the impact of COVID-19 on operative case numbers recorded by surgeons in training, and annual review of competency progression (ARCP) outcomes in the United Kingdom. Methods Anonymised operative logbook numbers were collated from e-logbook and ARCP outcome data were collated from the Interc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…Our findings are consistent with findings reported by Clement et al. for surgical trainees in their quantitative analysis of surgical logbooks [4]. In their study, they reported a reduction in the overall number of operative cases logged, with elective cases affected more than emergencies, a finding that was similar to that observed in our data.…”
Section: Figuresupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are consistent with findings reported by Clement et al. for surgical trainees in their quantitative analysis of surgical logbooks [4]. In their study, they reported a reduction in the overall number of operative cases logged, with elective cases affected more than emergencies, a finding that was similar to that observed in our data.…”
Section: Figuresupporting
confidence: 93%
“…While the volume of cases in most specialties reduced -ENT (À53.2%); orthopaedic (À50.7%); dental (À49.3%); gynaecology (À46.5%); general (À37.7%); plastics (À37.1%)there was an increase in some, including radiology (29.0%), neonates (17.7%) and vascular (29.0%). Our findings are consistent with findings reported by Clement et al for surgical trainees in their quantitative analysis of surgical logbooks [4]. In their study, they reported a reduction in the overall number of operative cases logged, with elective cases affected more than emergencies, a finding that was similar to that observed in our data.…”
supporting
confidence: 93%